Convergence Theory Related to The Language Ambassador Speaking English Ability - Eko Parias Saputra; Zohri Hamdani; Dyah Sih Pratiwi (Departement of Mathematics Education, 2023)
This study examines the convergence theory's applicability in the language acquisition process of two language ambassadors who possess excellent English speaking abilities. The research utilizes a qualitative method, employing in-depth interviews as the primary data collection tool. The respondents, Vina and Rafli, were selected based on their outstanding English proficiency demonstrated through language tests and academic achievements. Findings reveal that both internal factors (such as interest and talent) and external factors (such as supportive environments and learning facilities) significantly contribute to the respondents' language proficiency. The study concludes that the convergence theory accurately explains the language acquisition process in the cases of Vina and Rafli.